2022
DOI: 10.1128/spectrum.02361-21
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of the Host-Derived Cell-Wall Binding Domain of Endolysin CD16/50L as a Molecular Anchor in Preservation of Uninfected Clostridioides difficile for New Rounds of Phage Infection

Abstract: Endolysin is a peptidoglycan hydrolase encoded in a phage genome. The enzyme is attractive due to its potential use as antibacterial treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 100 publications
0
13
0
Order By: Relevance
“…The stationary phase cultures were then harvested by centrifugation at 6000× g for 5 min at 25 °C, washed once with sterile distilled water, and resuspended in 50 mM potassium phosphate (pH 7.5) and 10 mM 2-mercaptoethanol. Zymolyase-100T (0.4 units) (Zymo Research, Irvine, CA, USA) was added to cell suspensions and the absorbance at 600 nm was measured using a Multiskan SkyHigh (Thermo Fisher Scientific) every 5 min for 1 h [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The stationary phase cultures were then harvested by centrifugation at 6000× g for 5 min at 25 °C, washed once with sterile distilled water, and resuspended in 50 mM potassium phosphate (pH 7.5) and 10 mM 2-mercaptoethanol. Zymolyase-100T (0.4 units) (Zymo Research, Irvine, CA, USA) was added to cell suspensions and the absorbance at 600 nm was measured using a Multiskan SkyHigh (Thermo Fisher Scientific) every 5 min for 1 h [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, CBD may allow localization of the substrate (peptidoglycan) in the proximity of the catalytic site of the enzyme 132 ; on the other hand, it may anchor endolysins to peptidoglycan of post-lytic cell remnants, thus limiting their availability for other cells. 133 Accordingly, some recombinant endolysins have higher lytic activity when they lack CBD, whereas others have lower or no lytic activity. 129 , 134 Also, some studies indicate that EAD alone determines endolysin specificity, 135 which is somewhat broader compared with endolysins containing CBD.…”
Section: Phage-based Therapies Against C Difficile Infectionsmentioning
confidence: 99%
“…Of note, one common observation that has been reported with all C. difficile phage endolysins is that the catalytic domain of the enzyme alone (EAD) is sufficient for full activity. In fact, the removal of the CBD was reported to increase the lytic activity of C. difficile ( 30 32 , 36 , 38 ). It was also shown that the CBD from the CD16/50L endolysin was responsible for trapping the endolysin within cellular debris after lysis.…”
Section: Cell Wall-degrading Enzymes As Antimicrobialsmentioning
confidence: 99%
“…It was also shown that the CBD from the CD16/50L endolysin was responsible for trapping the endolysin within cellular debris after lysis. It was hypothesized that the CBD domain prevents the endolysin from being released freely into the environment upon cell lysis, therefore preserving uninfected bacteria that can serve as hosts for subsequent phage infection ( 36 ). Full-length endolysins were shown to be very specific toward C. difficile , as little or no activity was noted on other commensal bacteria, including related Clostridia.…”
Section: Cell Wall-degrading Enzymes As Antimicrobialsmentioning
confidence: 99%